Informationality of noise-like signals - Kolodiy, Zenoviy; Lazarenko, Nadiya (Видавництво Львівської політехніки, 2024)
With known methods of detecting and extracting a useful signal from a signal-noise mixture, another method of detecting an information signal is proposed – based on the analysis of the energy spectrum of such a mixture. Examples of informa- tional signals were noise-like signals generated by operators. The white noise signal was generated with a computer. The statistical parameters of the signals of the operators and the computer – average value, variance – were commensurate. The analysis of the operators’ signals showed that with sufficient duration of these signals, their energy spectrum is similar to flicker noise. The energy spectra of most signals generated by natural dynamic systems are similar to the form of flicker noise. The informativeness of operator signals, white noise, and additive signal-noise mixture was evaluated by the value of entropy, which was determined by the parameter τ of the approximating function of the energy spectrum. At the same time, the amount of information in white noise is zero, and the amount of information in noisy signals of operators is greater, the smaller the value of τ is.
Keywords: Energy spectrum of signals; Noise-like signals; Amount of information; Flicker noise